PulmOnary vein isolation With vs. without continued antiarrhythmic Drug trEatment in subjects with Recurrent Atrial Fibrillation (POWDER AF): results from a multicentre randomized trial. (2nd December 2017) - Duytschaever, Mattias; Demolder, Anthony; Phlips, Thomas; Sarkozy, Andrea; El Haddad, Milad; Taghji, Philippe; Knecht, Sebastien; Tavernier, Rene; Vandekerckhove, Yves; De Potter, Tom
Abstract: Aims: Catheter ablation is indicated in patients with symptomatic paroxysmal atrial fibrillation (AF) resistant to antiarrhythmic drug therapy (ADT). We investigated whether continued use of previously ineffective ADT beyond the post-ablation blanking period reduces recurrence of atrial tachyarrhythmia within the 1st year after ablation. Methods and results: This was a multicentre, randomized controlled study in patients undergoing contact force-guided pulmonary vein isolation (PVI) for paroxysmal AF in whom previously ineffective ADT was continued during a blanking period of 3 months. If free of AF at the end of the blanking period, patients were randomly assigned in the ratio of 1:1 to continue ADT (ADT ON group, n = 77) or discontinue ADT (ADT OFF group, n = 76). Patients were followed up until 1 year after PVI, with clinical visits, Holter monitoring, and quality-of-life (QOL) questionnaires at 6 and 12 months post-procedure. Analysis of the primary endpoint (any documented atrial tachyarrhythmia lasting >30 s) was performed according to the modified intention-to-treat principle. Secondary endpoints included repeat ablation, unscheduled visits, and QOL score. Baseline clinical characteristics and initial ablation procedure characteristics were comparable between both groups. Three patients were lost to follow-up in each arm. The primary endpoint was observed in 2 of 74 (2.7%) patients in the ADT ON group vs. 16 of 73 (21.9%) patients in the ADT OFF group ( P < 0.001). The ADT ON group had a lower rate of repeat ablation [1.4% vs. 19.2%, hazard ratio (HR) = 0.053; 95% confidence interval (CI) 0.007–0.399; P < 0.01) and less unscheduled arrhythmia-related health care visits (2.7% vs. 20.5%, HR = 0.055, 95% CI 0.007–0.410; P < 0.01). Quality-of-life scores were similar in both groups. Conclusion: In patients free of AF at the end of 3 months of post-ablation blanking period, continued use of previously ineffective ADT significantly reduces the recurrence of atrial tachyarrhythmia in the 1st year after PVI.